2020
DOI: 10.3390/en13143705
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Connectedness in Clean Energy Stocks

Abstract: This paper examines the dynamics of connectedness among the realized volatility indices of 16 clean energy stocks belonging to the SPGCE and the implied volatility indices of two important stock markets—the S&P 500 and the STOXX50—and two commodities markets—the crude oil and gold markets. The empirical results show a unidirectional connectedness from the implied volatility indices to the clean energy stocks. Our analysis further reveals similar volatility connectedness behaviors among companies in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
(82 reference statements)
1
10
0
1
Order By: Relevance
“…Most recent studies concentrated on the direct relationship between oil price changes and clean energy stock indices (Yu-Ling Hsiao et al, 2019;Dominioni et al, 2019;Fuentes and Herrera, 2020;Lv et al, 2021;Di Febo et al, 2021;Dawar et al, 2021;Ghabri et al, 2021). Most of these works found a significant oil price spillover effect on clean energy stock prices.…”
Section: Crude Oil Emission Allowance Price and Clean Energy Stock Ma...mentioning
confidence: 99%
“…Most recent studies concentrated on the direct relationship between oil price changes and clean energy stock indices (Yu-Ling Hsiao et al, 2019;Dominioni et al, 2019;Fuentes and Herrera, 2020;Lv et al, 2021;Di Febo et al, 2021;Dawar et al, 2021;Ghabri et al, 2021). Most of these works found a significant oil price spillover effect on clean energy stock prices.…”
Section: Crude Oil Emission Allowance Price and Clean Energy Stock Ma...mentioning
confidence: 99%
“…A strand of the literature has argued that the green/brown compartmentalization for a class of assets is not homogenous (e.g., see Fuentes and Herrera 2020 ; Kuang 2021a , b ). As such, there is the possibility that this classification might have implications for empirical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting extension of our work would be to study different clean energy markets. The literature (Fuentes & Herrera, 2020;Pham, 2019) has confirmed that different clean energy markets have heterogeneous spillovers to other markets. In addition, future research could examine the tail spillover among markets instead of the average spillover.…”
Section: Discussionmentioning
confidence: 98%